METHODOLOGICAL PRINCIPLES OF STUDY STUDY FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS - O.O. Havrylyuk (Освітній вимір, 2002)
In clause the advantages and lacks of various methods of testing of a state of communicative culture of the future teachers are opened.